Findings from a qualitative analysis: Social media influencers of color as trusted messengers of HPV vaccination messages - Amelia Burke-Garcia; Erin Cutroneo; Dasha Afanaseva; Kayla Madden; Angela Sustaita-Ruiz; Preethi Selvan; Estefany Rivera Sanchez; Amy Leader (PLoS ONE, 2025)
Background Despite HPV vaccination reducing the prevalence of cervical cancer by 90%, vaccination rates remain lower among communities of color due to vaccine hesitancy and mistrust in traditional public health messengers. The emergence of social media influencers, a newer kind of messenger, presents a unique opportunity to share immunization messages in new ways with a variety of communities. This paper reviews the qualitative findings from a study aimed at assessing influencers’ perceptions of and approaches to sharing messaging about the HPV vaccine. Methods Guided by several theories (Theory of Planned Behavior, Narrative Theory, and Opinion Leader Theory), the study team designed an intervention-based study consisting of qualitative interviews and social media influencer-designed and disseminated messaging. We worked closely with an influencer marketing firm to recruit 10 influencers of color who had children aged 9-14 – to write about the vaccine with their followers. Influencers used a provided factsheet to draft social media posts about vaccinating their children against HPV. Influencers were interviewed about their post and posts and interview transcripts were analyzed for key themes. Results Most influencers were hesitant to talk about vaccinations for fear of backlash. Most committed to writing, however, because they were compelled to support important health topics. All used the power of storytelling to convey the messages and highlighted their personal journeys of vaccine decision making. Influencers also highlighted the struggles of parenting and talked emotionally about how making decisions about this vaccine prompted feelings about their child growing up. Influencers also believed that they could help people make the decision to vaccinate. Conclusions The findings from this study elucidates the emotional context within which parents are being asked to vaccinate their children and thus, how personal the decision to vaccinate is. Most influencers noted that they had received a doctor’s recommendation but were taking the time to do their own research. Insights from this study can help inform current and future public health communication programs aimed at supporting immunization efforts. It also can provide lessons for other health topics.